Quick color-changing anti-dazzling rearview mirror lens and preparation method thereof

By using composite enhancement additives of rare earth element mixture and mixed auxiliary agents in the electrochromic coating production process, the problem of poor bonding between the coatings is solved, and the high stability of the fast color change and anti-glare rearview mirror lens is achieved. and quick response effects.

CN119118535APending Publication Date: 2024-12-13SHANGHAI BOLSON AUTO PARTS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411278064.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing electrochromic coatings have poor bonding between coatings during the production process, resulting in poor structural stability and short service life, which affects the application effect of anti-glare rearview mirrors.

Method used

Before sputtering deposition, spray composite reinforcement additives on the glass base surface, including rare earth element mixture and mixing auxiliary agents. The rare earth element mixture consists of lanthanum, yttrium and cerium, and mixing auxiliary agents consist of potassium tartrate and sodium citrate. The binding stability between the plating is improved through the nanoparticle strengthening mechanism.

Benefits of technology

It significantly improves the bonding stability of multiple coatings, achieves rapid color change reaction time (within 7 seconds), enhances anti-glare effect and application stability, and extends service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005040832830000081
    Figure BDA0005040832830000081
  • Figure BDA0005040832830000091
    Figure BDA0005040832830000091
Patent Text Reader

Abstract

The invention relates to the technical field of automobile parts, and particularly discloses a quick color-changing anti-dazzling rearview mirror lens which comprises a glass substrate and a coating film on the glass substrate, and the coating film comprises a transparent conductive layer, an electrochromic layer, an ion conduction layer, an ion storage layer, a reflective conductive layer and a protective layer which are sequentially sputtered and deposited on the glass substrate; before sputtering deposition of a transparent conductive layer, an electrochromic layer, an ion conduction layer, an ion storage layer, a reflective conductive layer and a protective layer, a composite reinforcing auxiliary is sprayed on a sputtering deposition base surface, and the composite reinforcing auxiliary comprises the following components in parts by weight: 8-12 parts of a rare earth element mixture; 0.5 to 1.5 parts of a mixed auxiliary agent; the rare earth element mixture consists of lanthanum, yttrium and cerium; and the mixed auxiliary agent consists of potassium tartrate and sodium citrate. According to the quick-color-changing anti-dazzling rearview mirror lens, the high response speed of the anti-dazzling effect can be maintained in the lasting application process, the quick-color-changing requirement is met, and the overall application stability is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of automobile accessories, and more specifically, to a fast-discoloring anti-glare rearview mirror lens and a preparation method thereof. Background Art

[0002] The rearview mirror is a tool for the driver to directly obtain external information such as the rear, side and bottom of the car while sitting in the cab seat. It is mainly used in the automotive industry to improve driving safety. Among them, the anti-glare rearview mirror of the car can reduce the reflection of light when encountering strong light, thereby protecting the driver's eyesight and increasing driving safety, especially at night or in poor light conditions, which can improve the driver's field of vision and safety.

[0003] For example, the invention patent application document with patent publication number CN113755805A records a curved surface coating process for electrochromic lenses, including the following steps: step one, thermally bending the substrate and the cover glass; step two, forming an electrochromic coating on the substrate by magnetron sputtering; step three, bonding the cover glass to the substrate with an adhesive, wherein step two includes spraying a first transparent electrode layer, spraying an electrochromic layer, spraying an ion conductive layer, spraying an ion storage layer, and spraying a second transparent electrode layer, and an eccentric circular cylindrical target is used for spraying.

[0004] Regarding the above-mentioned related technologies, the inventors believe that in the production process of the electrochromic coating, it can be seen that it is formed by the accumulation of multiple layers of sputtering deposition coatings. In order to maintain better bonding between the multiple coatings, the sputtering deposition conditions of the coatings are often required to be high. If one of the coatings has defects, the final electrochromic coating film will perform poorly in overall structural stability, which will in turn affect its long-term stability during application, resulting in a significantly poor service life.

[0005] Therefore, it is urgent to propose a solution to solve the above technical problems. Summary of the invention

[0006] In order to improve the bonding stability of multiple coatings, better deal with coating defects, and thus ensure the application stability of anti-glare rearview mirrors, the present application provides a fast-changing anti-glare rearview mirror lens and a preparation method thereof.

[0007] In a first aspect, the present application provides a fast-changing color anti-glare rearview mirror lens, which adopts the following technical solution: a fast-changing color anti-glare rearview mirror lens, comprising a glass substrate and a coating film on the glass substrate, wherein the coating film comprises a transparent conductive layer, an electrochromic layer, an ion conductive layer, an ion storage layer, a reflective conductive layer and a protective layer sequentially sputtered and deposited on a glass substrate; before performing sputtering deposition of the transparent conductive layer, the electrochromic layer, the ion conductive layer, the ion storage layer, the reflective conductive layer and the protective layer, a composite reinforcing agent is sprayed on the sputtering deposition base surface, wherein the composite reinforcing agent comprises the following components in parts by weight: 8-12 parts of rare earth element mixture; Mixing auxiliary agent 0.5-1.5 parts; The rare earth element mixture is composed of lanthanum, yttrium and cerium in a weight ratio of (6-8):(3.5-4):1; The mixed auxiliary agent is composed of potassium tartrate and sodium citrate in a weight ratio of (1.3-1.7):1.

[0008] By adopting the above technical scheme, since a transparent conductive layer, an electrochromic layer, an ion conduction layer, an ion storage layer, a reflective conductive layer and a protective layer are used as coating films on a glass substrate, after power is turned on, the ion layers before the film layers are used to move relative to each other, thereby achieving color change, absorbing strong light and preventing glare, and being able to achieve a color change reaction time of less than 7 seconds, thereby solving the problem of glare caused by strong light reflection when the driver observes the rearview mirror when there is a vehicle coming from behind, and reducing the occurrence of traffic accidents.

[0009] In order to ensure stable and excellent bonding between multiple coatings, a composite reinforcing agent is sprayed on the sputtering deposition base surface before sputtering deposition. The nano-particle strengthening mechanism is used to not only bring about toughening and crack resistance, but also effectively transfer loads and maintain the stability of interface bonding. Among them, lanthanum in the rare earth element mixture can improve the wettability of the coating material, thereby enhancing the interaction between the coating and the substrate; yttrium has a high magnetic permeability, which can improve the sensing and storage performance of the material in electromagnetic devices, and has excellent optical properties, and can be preferentially adsorbed on the surface defects of the substrate, bringing about a transition effect, which is conducive to the subsequent sputtering deposition to form a stable coating; cerium can transform the coating structure from amorphous to microcrystalline and crystalline, and can increase the interaction between coatings; the use of lanthanum, yttrium and cerium to form a rare earth element mixture can play an excellent synergistic role between multiple coatings and significantly improve the bonding stability between multiple coatings. At the same time, the use of rare earth element mixture is also matched with a mixed auxiliary agent composed of potassium tartrate and sodium citrate. The mixed auxiliary agent has a regulatory effect on the deposition of the coating during the sputtering deposition process, which is beneficial to the crystallization refinement of the coating, and maintains a tight structure between the rare earth element mixture and the coating, ensuring that the composite reinforcing auxiliary agent exerts a more excellent effect, thereby making the obtained fast-changing color anti-glare rearview mirror lens have significantly excellent application stability.

[0010] Preferably, the rare earth element mixture consists of lanthanum, yttrium and cerium in a weight ratio of 6.8:3.7:1.

[0011] By adopting the above technical scheme, when lanthanum, yttrium and cerium in the above weight ratio are used to form a rare earth element mixture, their mutual coordination is better, the compounding effect brought about is relatively excellent, and they can be combined at the interface of the coating to fully exert the corresponding effect, which can not only better deal with coating defects, but also significantly improve the bonding stability of multiple coatings, thereby making the application stability performance of the fast-changing anti-glare rearview mirror lens better.

[0012] Preferably, the mixing auxiliary agent consists of potassium tartrate and sodium citrate in a weight ratio of 1.5:1.

[0013] By adopting the above technical scheme, when the potassium tartrate and sodium citrate in the above weight ratio are used as a mixed auxiliary agent, it can bring wetting effect to the base surface during the sputtering deposition process, which has a positive effect on improving the bonding strength between the coatings, so that the coating has better stability and adhesion, and assists the rare earth element mixture to form a more solid bonding structure with the coating, and finally the application stability of the fast-changing color anti-glare rearview mirror lens is also better.

[0014] Preferably, the weight ratio of the rare earth element mixture to the mixing auxiliary agent is 10:1.

[0015] By adopting the above technical scheme, when the rare earth element mixture and the mixed auxiliary agent are used in the above weight ratio to form a composite reinforcing auxiliary agent, the coordination between the two is better, and the interface bonding strength and interface bonding stability can be significantly enhanced at the coating bonding interface, thereby making the bonding stability of the multiple coatings better, which is conducive to obtaining a fast-changing anti-glare rearview mirror lens with better application stability.

[0016] Preferably, the spraying amount of the composite reinforcing agent is 0.15-0.45 g / m 2 .

[0017] By adopting the above technical solution, if the spraying amount is large, serious accumulation of rare earth element mixture will occur, and the more excellent nano-particle strengthening mechanism cannot be exerted; if the spraying amount is small, it cannot form a stable action mechanism with the coating structure, and it is difficult to effectively overcome the coating defects; and the above-mentioned spraying amount of composite reinforcing additives can ensure that it can fully act on the interface bonding of the coating and bring about a significant improvement in the stability of the interface bonding, thereby ensuring that the fast-changing color anti-glare rearview mirror lens has better application stability.

[0018] Preferably, the spraying amount of the composite reinforcing agent is 0.3 g / m 2 .

[0019] By adopting the above technical scheme, when the above-mentioned sprayed amount of composite reinforcing additive acts on the interface bonding of the coating, the rare earth element mixture and the mixed auxiliary agent contained therein can play a better corresponding coordination role, so that a relatively stable bond can be formed between the coatings, and finally an excellent quality fast-changing anti-glare rearview mirror lens can be obtained.

[0020] Preferably, the material of the transparent conductive layer is indium tin oxide; The side of the electrochromic layer close to the glass substrate is an inner layer, the material of which is tungsten oxide, and the side away from the glass substrate is an outer layer, the material of which is metallic lithium; The material of the ion conducting layer is any one of tantalum oxide and zinc oxide; The material of the ion storage layer is nickel tungsten oxide; The material of the reflective conductive layer is any one of metal chromium, titanium, aluminum and silver; The material of the protective layer is silicon dioxide.

[0021] By adopting the above technical scheme, the indium tin oxide transparent conductive layer can provide high transmittance and excellent conductivity; the electrochromic layer composed of tungsten oxide and metallic lithium can stably and reversibly change color and transparency under the action of an external voltage or electric field; the tantalum oxide ion conduction layer has excellent ion conduction characteristics, high ion conductivity and selectivity; the nickel tungsten oxide ion storage layer stores and provides ions required for electrochromism, maintains charge balance, and has high electron and ion transmission capacity; any one of metal chromium, titanium, aluminum, and silver as a reflective conductive layer can improve transmittance and conductivity; the silicon dioxide protective layer has excellent durability and environmental adaptability; and through the selection and coordination of the materials used for the above transparent conductive layer, electrochromic layer, ion conduction layer, ion storage layer, reflective conductive layer and protective layer, the coating film can undergo stable and reversible color changes under the action of an external electric field when used, and can achieve a color change reaction time of less than 7 seconds, with a high response speed of anti-glare effect, meet the requirements of rapid color change, and have excellent overall application quality.

[0022] Preferably, the glass substrate has a thickness of 0.1-5.0 mm and is in different shapes of a flat surface or a curved surface.

[0023] By adopting the above technical solution, the glass substrate of the above thickness and the above shape are suitable for the coating film bonding requirements, and the obtained fast-changing color anti-glare rearview mirror lens not only has a faster response and better anti-glare effect when used, but also can show excellent long-term application stability.

[0024] In a second aspect, the present application provides a method for preparing a fast-changing color anti-glare rearview mirror lens, using the following technical solution: A method for preparing a fast color-changing anti-glare rearview mirror lens comprises the following steps: (1) preparing a glass substrate, using vacuum coating technology to sequentially sputter-deposit a transparent conductive layer, an electrochromic layer, an ion conductive layer, an ion storage layer, a reflective conductive layer and a protective layer on the glass substrate, thereby forming a coating film on the glass substrate, and spraying a composite reinforcing agent on the sputtering deposition base surface before the sputtering deposition through each coating layer; (2) heat treating the semi-finished product obtained after the sputtering deposition in step (1) at a temperature of 100-400° C. for a time of 5-90 min to obtain a fast-changing color-resistant anti-glare rearview mirror lens.

[0025] By adopting the above technical solution, in the above preparation operation, heat treatment is performed after sputtering deposition is completed, which can not only make the coating film tightly bonded to the glass substrate, but also make the bonding between each coating layer deeper, so that the final fast-changing anti-glare rearview mirror lens has excellent structural stability and better overall application quality.

[0026] In summary, this application has the following beneficial effects: The present application uses a rare earth element mixture composed of lanthanum, yttrium and cerium, and a mixed auxiliary agent composed of potassium tartrate and sodium citrate to form a composite reinforcing auxiliary agent that is applied to the sputtering deposition base surface of the transparent conductive layer, electrochromic layer, ion conduction layer, ion storage layer, reflective conductive layer and protective layer. The bonding stability of multiple coatings can be significantly improved, thereby obtaining a fast-changing anti-glare rearview mirror lens with excellent application stability, which can maintain a high response speed of the anti-glare effect during long-term application and meet the requirements of fast color change, and the overall application quality is excellent. DETAILED DESCRIPTION

[0027] The present application is further described in detail below in conjunction with embodiments and comparative examples.

[0028] Unless otherwise specified, the raw materials used in the preparation examples, embodiments and comparative examples of the present application are commercially available: Indium tin oxide target was purchased from Beijing Jinyuan New Materials Technology Co., Ltd., with the catalog number JY1018; Tungsten oxide target was purchased from Beijing Jinyuan New Materials Technology Co., Ltd. Tungsten trioxide target, product number JY10311; The metal lithium target was purchased from Beijing Jinyuan New Material Technology Co., Ltd. The high-purity lithium target was JY1020; Tantalum oxide target was purchased from Baoji Yusheng Metal Technology Co., Ltd., brand Ta2; Nickel oxide tungsten target was purchased from Shijiazhuang Dongming New Materials Technology Co., Ltd. Specification 4N; The metallic chromium target was purchased from Beijing Jinyuan New Material Technology Co., Ltd., with the item number JY1009; Silica targets were purchased from Shijiazhuang Dongming New Materials Technology Co., Ltd., product grade 5N; The glass substrate was purchased from Chengdu Huihuang Mingzhu Glass Co., Ltd. as clear tempered glass with the item number HG-8. Example

[0029] Example 1 A fast color-changing anti-glare rearview mirror lens comprises a glass substrate and a coating film on the glass substrate, wherein the coating film comprises a transparent conductive layer, an electrochromic layer, an ion conductive layer, an ion storage layer, a reflective conductive layer and a protective layer which are sequentially sputtered and deposited on the glass substrate, and is prepared by the following method: (1) preparing a glass substrate, using vacuum coating technology to sequentially sputter-deposit a transparent conductive layer, an electrochromic layer, an ion conductive layer, an ion storage layer, a reflective conductive layer and a protective layer on the glass substrate, thereby forming a coating film on the glass substrate, and spraying a composite reinforcing agent on the sputtering deposition base surface before the sputtering deposition through each coating layer; (2) The semi-finished product obtained after the sputtering deposition in step (1) is heat treated at a temperature of 100-400° C. (preferably 300° C. in this embodiment) for a time of 5-90 min (preferably 40 min in this embodiment) to obtain a fast-changing color-resistant anti-glare rearview mirror lens.

[0030] Note: The components and corresponding weights of the composite reinforcement additive are shown in Table 1. The spraying amount of the composite reinforcement additive is 0.3g / m 2 The composite reinforcing agent is obtained by mixing a rare earth element mixture and a mixed auxiliary agent, wherein the rare earth element mixture is composed of lanthanum, yttrium and cerium in a weight ratio of 6.8:3.7:1; and the mixed auxiliary agent is composed of potassium tartrate and sodium citrate in a weight ratio of 1.5:1. The glass substrate has a thickness of 3 mm and is in a flat shape.

[0031] The material of the transparent conductive layer is indium tin oxide; The side of the electrochromic layer close to the glass substrate is the inner layer, the material of which is tungsten oxide, and the side away from the glass substrate is the outer layer, the material of which is metallic lithium; The material of the ion conducting layer is silicon oxide; The material of the ion storage layer is nickel tungsten oxide; The material of the reflective conductive layer is metal chromium; The material of the protective layer is silicon dioxide; The above coatings are obtained by sputtering deposition of the corresponding target materials. During the sputtering deposition process, the target material is first fed into the sputtering chamber, the distance between the target material and the substrate is first controlled to 5 cm, and then the vacuum is evacuated to 1.0×10 -3Pa, and then argon was introduced; first, argon was ionized at 200V to produce glow discharge, and then argon and oxygen were introduced at a volume ratio of 1:8 to control the sputtering pressure to 1.6Pa, and then 40mA / cm 2 The sputtering was carried out at a current density of 1.8 nm / min and a deposition rate of 1.8 nm / min.

[0032] Finally, the thickness of the indium tin oxide layer is 75 μm, the thickness of the tungsten oxide layer is 60 μm, the thickness of the metal lithium layer is 80 μm, the thickness of the silicon oxide layer is 80 μm, the thickness of the nickel tungsten oxide layer is 40 μm, the thickness of the metal chromium layer is 75 μm, and the thickness of the silicon dioxide layer is 85 μm.

[0033] Example 2-3 A fast-changing color anti-glare rearview mirror lens is different from Preparation Example 1 in that the components of the composite reinforcing auxiliary agent used and their corresponding weights are shown in Table 1.

[0034] Table 1 Composite reinforcement auxiliary components used in Examples 1-3 and their corresponding weights (kg / part) Components Example 1 Example 2 Example 3 Rare earth element mixture 10 8 12 Mixing auxiliary agent 1 0.5 1.5 Example 4 A fast-changing color anti-glare rearview mirror lens is different from Preparation Example 1 in that the rare earth element mixture consists of lanthanum, yttrium and cerium in a weight ratio of 7:3.75:1.

[0035] Example 5 A fast-changing color anti-glare rearview mirror lens is different from Preparation Example 1 in that the rare earth element mixture consists of lanthanum, yttrium and cerium in a weight ratio of 6:3.5:1.

[0036] Example 6 A fast-changing color anti-glare rearview mirror lens is different from Preparation Example 1 in that the rare earth element mixture consists of lanthanum, yttrium and cerium in a weight ratio of 8:4:1.

[0037] Example 7 A fast-changing color anti-glare rearview mirror lens is different from Preparation Example 1 in that the mixed auxiliary agent consists of potassium tartrate and sodium citrate in a weight ratio of 1.3:1.

[0038] Example 8 A fast-changing color anti-glare rearview mirror lens is different from Preparation Example 1 in that the mixed auxiliary agent consists of potassium tartrate and sodium citrate in a weight ratio of 1.7:1.

[0039] Example 9 A fast color-changing anti-glare rearview mirror lens, which is different from Preparation Example 1 in that the spraying amount of the composite reinforcing additive is 0.15 g / m 2 .

[0040] Example 10 A fast color-changing anti-glare rearview mirror lens, which is different from Preparation Example 1 in that the spraying amount of the composite reinforcing additive is 0.45 g / m 2 .

[0041] Embodiment 11 A fast-changing color anti-glare rearview mirror lens is different from Preparation Example 1 in that the glass substrate is in a curved shape with a curvature of 0.15%.

[0042] Example 12 A fast color-changing anti-glare rearview mirror lens, which is different from Preparation Example 1 in that the spraying amount of the composite reinforcing additive is 0.1 g / m 2 .

[0043] Embodiment 13 A fast color-changing anti-glare rearview mirror lens, which is different from Preparation Example 1 in that the spraying amount of the composite reinforcing additive is 0.5 g / m 2 .

[0044] Embodiment 14 A fast-changing color anti-glare rearview mirror lens is different from Preparation Example 1 in that the weight ratio of the rare earth element mixture to the mixing auxiliary agent is 10:0.8.

[0045] Embodiment 15 A fast color-changing anti-glare rearview mirror lens, which is different from Preparation Example 1 in that the weight ratio of the rare earth element mixture to the mixed auxiliary agent is 10.5:1 Comparative Example Comparative Example 1 A fast-changing color anti-glare rearview mirror lens is different from Preparation Example 1 in that the composite reinforcing auxiliary agent used does not contain a rare earth element mixture.

[0046] Comparative Example 2 A fast-changing color anti-glare rearview mirror lens is different from Preparation Example 1 in that the composite reinforcing auxiliary agent used does not contain a mixed auxiliary agent.

[0047] Comparative Example 3 A fast-changing color anti-glare rearview mirror lens is different from Preparation Example 1 in that no composite reinforcing auxiliary agent is used.

[0048] Comparative Example 4 A fast-changing color anti-glare rearview mirror lens, which is different from Preparation Example 1 in that lanthanum is not included in the rare earth element mixture.

[0049] Comparative Example 5 A fast-changing color anti-glare rearview mirror lens, which is different from Preparation Example 1 in that yttrium is not included in the rare earth element mixture.

[0050] Comparative Example 6 A fast-changing color anti-glare rearview mirror lens, which is different from Preparation Example 1 in that cerium is not included in the rare earth element mixture.

[0051] Comparative Example 7 A fast-changing color anti-glare rearview mirror lens, which is different from Preparation Example 1 in that lanthanum and cerium are not included in the rare earth element mixture.

[0052] Comparative Example 8 A fast-changing color anti-glare rearview mirror lens, which is different from Preparation Example 1 in that yttrium and cerium are not included in the rare earth element mixture.

[0053] Comparative Example 9 A fast-changing color anti-glare rearview mirror lens, which is different from Preparation Example 1 in that lanthanum and yttrium are not included in the rare earth element mixture.

[0054] Performance test samples: The fast color-changing anti-glare rearview mirror lens obtained in Application Example 1-15 is used as Test Sample 1-15, and the fast color-changing anti-glare rearview mirror lens obtained in Comparative Example 1-9 is used as Control Sample 1-9.

[0055] Test method: Test samples 1-15 and control samples 1-9 were tested for tinting conversion time according to the standard "JC / T 2631-2021 Electrochromic Glass". Each sample was tested three times and the average value was recorded as the initial value t0.

[0056] The test samples 1-15 and control samples 1-9 that have completed the above tests are then subjected to a high-voltage accelerated aging life test in accordance with the content of the standard "T / ZZB 2870-2022 Electrochromic Anti-glare Rearview Mirror Lenses". The test steps are as follows: a) Set the temperature of the high pressure accelerated aging test chamber to (121±2)°C and the saturated vapor pressure range to 14psi to 18psi; b) One cycle is 24 hours (saturated steam for 20 hours, then take out and let stand at 25℃ for 4 hours); c) Repeat the above steps for 7 cycles of testing.

[0057] The same method is used to test the color conversion time of the test samples 1-15 and the control samples 1-9 that have completed the high-voltage accelerated aging life test, and the results are recorded as t1.

[0058] The growth rate of the tinting conversion time is calculated, and the growth rate = (t1-t0) / t0; the greater the growth rate of the tinting conversion time, the worse the bonding stability of the multi-coating is, and the worse the application stability of the fast-changing anti-glare rearview mirror lens is.

[0059] Table 2 Test results of test samples 1-15 and control samples 1-9 Combining Examples 1-3 and Comparative Examples 1-3 and Table 2, it can be seen that when the rare earth element mixture and the mixed auxiliary agent are mixed to form a composite reinforcing auxiliary agent and applied to the fast-changing color anti-glare rearview mirror lens, after completing the above test, the color conversion time growth rate can be significantly reduced, indicating that the combination stability of the multi-layer is better, and the application stability of the fast-changing color anti-glare rearview mirror lens is also relatively excellent; and if any one of the rare earth element mixture and the mixed auxiliary agent is used alone as a composite reinforcing auxiliary agent, it is found that the corresponding effects brought are limited, and the sum of the corresponding effects brought by each use is far less than the excellent effect brought by the compounding of the two. It can be seen that the cooperation between the rare earth element mixture and the mixed auxiliary agent brings a significant effect of 1+1>2. Combining Examples 14-15 and Table 2, it can be seen that when the weight ratio of the rare earth element mixture and the mixed auxiliary agent is 10:1, a fast-changing color anti-glare rearview mirror lens with better application stability can be obtained.

[0060] It can be seen from Example 1 and Example 4-6 and Table 2 that when lanthanum, yttrium and cerium form a rare earth element mixture, they can all be combined at the interface of the coating to give full play to the corresponding effect and significantly improve the bonding stability of the multi-coating. When lanthanum, yttrium and cerium are used in a weight ratio of 6.8:3.7:1 to form a rare earth element mixture, the corresponding effect is relatively excellent, and the color conversion time growth rate obtained by testing is relatively good. It can be seen from Comparative Examples 1 and 4-9 and Table 2 that if any one or two of lanthanum, yttrium and cerium are mixed with a mixed auxiliary agent as a composite reinforcing auxiliary agent, the effect of improving the bonding stability of the coating is limited, and the corresponding effects are only simply superimposed on each other, and it is even more impossible to play a compound synergistic effect with the mixed auxiliary agent. Only when lanthanum, yttrium and cerium are compounded as a rare earth element mixture, can a more significant application effect be brought, and the color conversion time growth rate obtained by testing is also relatively low, indicating that the application stability of the fast color-changing anti-glare rearview mirror lens is better.

[0061] Combining Example 1 with Examples 9-10 and Table 2, it can be seen that the spraying amount of the composite reinforcing additive is 0.15-0.45 g / m 2When the spraying amount is lower or higher than the above range, it is found that the growth rate of the color conversion time obtained by the test will increase significantly, indicating that the composite reinforcing additive is difficult to form a relatively stable bond between the coatings.

[0062] It can be seen from Example 1 and Example 11 and Table 2 that the different shapes of the glass substrate, whether it is a flat surface or a curved surface, do not affect the acquisition of a fast-changing anti-glare rearview mirror lens with excellent application stability.

[0063] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A fast color changing anti-glare rearview mirror lens, characterized in that: The invention comprises a glass substrate and a coating film on the glass substrate, wherein the coating film comprises a transparent conductive layer, an electrochromic layer, an ion conductive layer, an ion storage layer, a reflective conductive layer and a protective layer which are sequentially sputtered and deposited on a glass substrate; before performing sputtering deposition of the transparent conductive layer, the electrochromic layer, the ion conductive layer, the ion storage layer, the reflective conductive layer and the protective layer, a composite reinforcing agent is sprayed on the sputtering deposition base surface, wherein the composite reinforcing agent comprises the following components in parts by weight: 8-12 parts of rare earth element mixture; Mixing auxiliary agent 0.5-1.5 parts; The rare earth element mixture is composed of lanthanum, yttrium and cerium in a weight ratio of (6-8): (3.5-4): 1; The mixed auxiliary agent is composed of potassium tartrate and sodium citrate in a weight ratio of (1.3-1.7):

1.

2. The fast color changing anti-glare rearview mirror lens according to claim 1, characterized in that: The rare earth element mixture consists of lanthanum, yttrium and cerium in a weight ratio of 6.8:3.7:

1.

3. The fast color changing anti-glare rearview mirror lens according to claim 1, characterized in that: The mixed auxiliary agent is composed of potassium tartrate and sodium citrate in a weight ratio of 1.5:

1.

4. The fast color changing anti-glare rearview mirror lens according to claim 1, characterized in that: The weight ratio of the rare earth element mixture to the mixing auxiliary agent is 10:

1.

5. The fast color changing anti-glare rearview mirror lens according to claim 1, characterized in that: The spraying amount of the composite reinforcement additive is 0.15-0.45g / m 2 .

6. The fast color changing anti-glare rearview mirror lens according to claim 5, characterized in that: The spraying amount of the composite reinforcement additive is 0.3g / m 2 .

7. The fast color changing anti-glare rearview mirror lens according to claim 1, characterized in that: The material of the transparent conductive layer is indium tin oxide; The side of the electrochromic layer close to the glass substrate is an inner layer, the material of which is tungsten oxide, and the side away from the glass substrate is an outer layer, the material of which is metallic lithium; The material of the ion conducting layer is any one of tantalum oxide and zinc oxide; The material of the ion storage layer is nickel tungsten oxide; The material of the reflective conductive layer is any one of metal chromium, titanium, aluminum and silver; The material of the protective layer is silicon dioxide.

8. The fast color changing anti-glare rearview mirror lens according to claim 1, characterized in that: The glass substrate has a thickness of 0.1-5.0 mm and is in different shapes of a flat surface or a curved surface.

9. The method for preparing the fast color-changing anti-glare rearview mirror lens according to claim 1, characterized in that: The following steps are involved: (1) preparing a glass substrate, and using vacuum coating technology to sequentially sputter-deposit a transparent conductive layer, an electrochromic layer, an ion conductive layer, an ion storage layer, a reflective conductive layer, and a protective layer on the glass substrate, thereby forming a coating film on the glass substrate, and spraying a composite reinforcing agent on the sputtering deposition base surface before sputtering deposition through each coating layer; (2) The semi-finished product obtained after the sputtering deposition in step (1) is subjected to heat treatment at a temperature of 100-400° C. for a time of 5-90 min to obtain a fast-changing color-resistant anti-glare rearview mirror lens.

Citation Information

Patent Citations

  • All solid state electrochromic anti -dazzle rear -view mirror

    CN207586602U

  • Electrochromic devices having n-doped conductive polymer as transparent conducting layer, ion storage layer, and / or electrochromic layer

    EP4365262A1

  • Electrochromic devices

    IN201827031213A